Steroid treatment for alopecia: development of cushing's syndrome during recovery - A clinical case report - Cakiroglu O. F.; Calişir S. N.; KALKAN E.; TAŞLIDERE B. (My University, 2026)
A 20-year-old male patient presented to the emergency department with nausea, back pain, confusion, tremors, and pink-purple lesions on his body. The patient had been using 64 milligrams of methylprednisolone for 13 months for the treatment of autoimmune alopecia, after which the dose was reduced to 16 milligrams. Over time, he experienced hair regrowth, weight gain, and the development of lesions, which he attributed to weight gain. However, in the past week, he developed muscle weakness, balance problems, cognitive issues, and bone pain. The patient recognized that these symptoms were related to steroid use and reduced his dose to 4 milligrams. Physical examination revealed striae, abdominal fat accumulation, buffalo hump, and bruising, all indicative of iatrogenic Cushing\"s syndrome. Laboratory results showed mild abnormalities. Following an endocrinology consultation, his methylprednisolone dose was adjusted to 8 milligrams, and follow-up was planned. This case highlights the serious complications of prolonged steroid use, including cognitive dysfunction, myopathy, and Cushing\"s syndrome, emphasizing the importance of individualized treatment protocols and regular monitoring to minimize side effects.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; Glucocorticoid side effects; Iatrogenic Cushing's syndrome; Steroid Myopathy